Learner’s beliefs : a case study of adult immigrants independently learning Finnish as a second language - Siren, Maricris (2021)
Learners’ beliefs about second language acquisition (SLA) are described as learners’ personal theories about language learning and language in general. Previous studies reported that beliefs can be productive or unproductive and influence learners’ behaviour such as self-directed learning (SDL). The purpose of the study is to explore the learners’ beliefs that adult immigrants hold about learning the Finnish language and their relation to SDL. The participants in this qualitative research are three adult immigrants in Finland learning Finnish outside formal institutions. Learning diaries were collected from the participants for two to seven months. Triangulation was implemented using open-ended questionnaires and asynchronous email interviews. The data were analysed using thematic analysis, followed by relational analysis. Findings reveal that the set of learners’ beliefs about Finnish language learning are (1) beliefs about self-sovereignty in language learning, (2) beliefs about volition situated in the learner’s context, and (3) beliefs about language learning as an organic experience. These beliefs were interpreted from the participants’ view about the importance of autonomous learning, sustaining motivation through effort, and second language learning in a natural way. The relational analysis results show that the relationship between the learners’ beliefs and SDL are interactive and reciprocal. Learners’ beliefs about learning the Finnish language independently are intricately linked to participants’ self-concepts and identity. The results suggest that the influence of learners’ situational context to learners’ beliefs are significant in understanding the unique psychology of an individual language learner.